1998
DOI: 10.1016/s0954-6111(98)90008-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent air-leak in spontaneous pneumothorax — clinical course and outcome

Abstract: Persistent air-leak in patients with spontaneous pneumothorax (SP) is not uncommon and may present a management dilemma in those who are unfit or unwilling for surgery. Video-assisted thoracoscopic surgery (VATS) has been advocated in the management of patients with broncho-pleural fistulae (air-leak persisting beyond 7 days): however the optimum time for surgical intervention remains unclear. We reviewed the records of 130 episodes of SP in 115 patients over a 2-year period to determine clinical course and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
106
4
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 13 publications
4
106
4
2
Order By: Relevance
“…The prevalence of PAL (14.9%) and ipsilateral recurrence (14.4%) in our study was similar to those reported in the literature. 11,14) As the recurrence rates have been reported to be 54% within four years after the first attack, it can be thought that the recurrence rate in our study might be increased after long follow-up period. 15) Bulla/bleb resection and wide pleural abrasion was applied to our patients via AT or VATS.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The prevalence of PAL (14.9%) and ipsilateral recurrence (14.4%) in our study was similar to those reported in the literature. 11,14) As the recurrence rates have been reported to be 54% within four years after the first attack, it can be thought that the recurrence rate in our study might be increased after long follow-up period. 15) Bulla/bleb resection and wide pleural abrasion was applied to our patients via AT or VATS.…”
Section: Discussionmentioning
confidence: 62%
“…3,12) This may suggest that simple tube drainage is an unsatisfactory treatment for even a first episode of PSP, particularly in the presence of a large pneumothorax, lifestyle or medical factors that would make recurrence especially dangerous. 13) Chee, et al 14) observed PAL in 25% of the cases with PSP. In our study, closed thoracic drainage was applied in all cases, and PAL was considered as air leak persisted longer than five days and cases with PAL or ipsilateral recurrence were operated.…”
Section: Discussionmentioning
confidence: 96%
“…Among patients with pneumothorax, 30 to 38% of them have recurrence (12). Although primary spontaneous pneumothorax usually resolves in 2 to 4 days of drainage, pneumothoraces in patients with underlying lung disease often last substantially longer (13). In our case, post-ARDS recurrent pneumothorax needed drainage for three weeks.…”
Section: Discussionmentioning
confidence: 66%
“…According to the literature, the recurrence rate is 16%-52%, based on the treatment method used for the first episode of spontaneous pneumothorax (29). Studies reporting higher recurrence rate in SSP than in PSP are available, although the reverse is also reported (30).…”
Section: Discussionmentioning
confidence: 99%